The little mermaid. Ariel's beginning [videorecording (DVD)] - Haaland, Kendra; Holmes, Peggy; Benson, Jodi; Hill Butters, Lorelei; Cummings, Jim, 1952-; Goris, Parker; Wright, Samuel E.; Field, Sally; Reese, Robert; Spiliotopoulos, Evan; Selbo, Jule, 1952-; Wingfield, Jenny (Disney DVD., 2008)
Long ago in a kingdom where music is outlawed, King Triton's youngest daughter Ariel discovers her love for music in a secret underground music club. Torn with the choice of whether to hide her passion or share it with her father and risk losing everything, Ariel sets off on a daring adventure to restore music to Atlantica.